Benefits of intraoperative cholangiogram for acute cholecystitis. Issue 3 (8th June 2021) - Askari, Alan; Riaz, Amjid A.; Brittain, Rory; Zhou, Joel; Irwin, Saskia; Talbot, Michael
Abstract: Background: Laparoscopic cholecystectomy is one of the most commonly performed surgical procedures in general surgery. The utility of intraoperative cholangiogram (IOC) and its role in reducing postoperative complications is as yet unclear. The aim of this study is to determine whether routine use of IOC in non‐elective laparoscopic cholecystectomy is associated with an improvement in outcome. Methods: Data were prospectively collected a single dedicated tertiary referral centre. All consecutive adult patients undergoing laparoscopic cholecystectomy on a non‐elective basis over a 6‐year period from October 2008 to December 2014 were included in the study. Chi squared analysis and multivariable logistic regression analyses were undertaken to determine the association between IOC and outcomes. Results: A total of 676 patients underwent non‐elective laparoscopic cholecystectomy over the study period, of whom 51.6% were male and the median age was 51 years old (IQR 37–68). The majority of the study population (84.6%, n = 572/676) underwent an IOC. The overall complication rate was 8.1% (n = 55/676), this was lower in the IOC group (6.1%) compared with the non‐IOC group (19.2%, P < .001). In particular, there was a lower rate of retained stones (1.6% vs 3.8%, P < .001), bleeding (0.0% vs 2.9%, P < .001) and conversion to open surgery (0.7% vs 7.7%, P < .001). Rates of CBD injury (0.0% vs 0.3%, P = .5465) and bile leak were similar across both groups (1.9% vs 0.9%). During multivariable logistic regression analysis, the use of IOC was independently associated with a reduced chance of complications (OR 0.27, 95% CI 0.15‐0.50, P < .001) as well as conversion to open (OR 0.11, 95% CI 0.03‐0.37, P < .001). Conclusion: In the context of laparoscopic cholecystectomy, IOC has a significant role to play. Our data show that it can reduce the likelihood of complications, retained stones and the need to convert to an open procedure. However, its routine use at present is difficult to justify given that the current study does not appear to make a difference in the most serious complications such as bile duct injury and bile leak. This study builds on previous work in justifying increased use of IOC during laparoscopic cholecystectomy.